2012
DOI: 10.1134/s0005117912080061
|View full text |Cite
|
Sign up to set email alerts
|

An iterative algorithm of adaptive output control with complete compensation for unknown sinusoidal disturbance

Abstract: Abstract-The problem is considered for the output control of a linear, parametrically indeterminate object subjected to the effect of an external unknown, sinusoidal disturbing influence. The solution of this problem is found in the class of iterative adaptive algorithms involving the channels of stabilization and identification of the frequency of a disturbing influence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Let us consider the output adaptive controller with modification for the input harmonic disturbance rejection introduced in [15]…”
Section: Output Controller Designmentioning
confidence: 99%
“…Let us consider the output adaptive controller with modification for the input harmonic disturbance rejection introduced in [15]…”
Section: Output Controller Designmentioning
confidence: 99%
“…A similar approach is pursuit in [13], where the analysis is restricted to minimum-phase systems of known relative degree, unaffected by measurement noise. Furthermore, in the cited reference no formal proof of convergence of the switching mecahnism is offered, apart from heuristic arguments.…”
Section: Introduction and Problem Formulationmentioning
confidence: 99%
“…It is also assumed that the plant model is stable and this property could be the result of a robust control design that is already incorporated in the system under consideration. The problem of disturbance rejection and adaptive regulation as defined above has been previously addressed in a number of papers ([3], [1], [7], [10], [11], [21], [16], [15], [6], [8], [2], [5]) among others. More recent references on the subject are [25], [17].…”
Section: Introductionmentioning
confidence: 99%
“…Several solutions have been proposed and the most successful has been based on the appropriate choice of the desired closed loop poles to be achieved by the Youla-Kučera central controller and by using an adjustable Q-FIR filter with the minimum number of parameters [4]. Recently in [13] it was suggested that over parametrization of the Q (FIR) filter can enhance the robustness of the linear and adaptive scheme in the vicinity of plant complex zeros 2 .…”
Section: Introductionmentioning
confidence: 99%